2016
DOI: 10.1208/s12249-016-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Biowaivers for Immediate Release Formulations Containing BCS III Drugs, Acyclovir, Atenolol, and Ciprofloxacin Hydrochloride, Using Dissolution Testing

Abstract: The dissolution of several products containing Biopharmaceutical Classification System (BCS) class III drugs, acyclovir, atenolol, and ciprofloxacin hydrochloride, listed in the WHO essential drug list (EDL), was tested and compared with their respective comparator pharmaceutical products (CPPs) marketed in South Africa and India. US Pharmacopeia (USP) buffers of pH 1.2, 4.5, and 6.8 were used as dissolution media and tested using USP apparatus 2 at 75 rpm and 900 ml. Nine acyclovir products were tested, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…OB and D2, which had different strength values ( fig. 3), had more than 85% of the drug released within 15 min, which revealed the finding that not only content of drugs and the manufacturing conditions, affect drug release but also formula factors, such as disintegrates and diluents types play an important part in the disintegration of tablet and dissolution profiles.Based on biowaiver study results, D1 sample in pH 7.8 is not bioequivalent with the OB unless further an in vivo bioequivalent studies prove that as it comparable to Reddy, N. H., et al, finding that some but not all Acyclovir, Atenolol, and Ciprofloxacin Hydrochloride products met the biowaiver criteria [35]. Excipients and additives used in manufacturing tablets have great effects on their dissolution, therefore to achieve biowaiver according to regulatory rules, good manufacturing practice should be followed and careful selection of the excipients used is mandatory.…”
Section: Dissolution Studiesmentioning
confidence: 88%
“…OB and D2, which had different strength values ( fig. 3), had more than 85% of the drug released within 15 min, which revealed the finding that not only content of drugs and the manufacturing conditions, affect drug release but also formula factors, such as disintegrates and diluents types play an important part in the disintegration of tablet and dissolution profiles.Based on biowaiver study results, D1 sample in pH 7.8 is not bioequivalent with the OB unless further an in vivo bioequivalent studies prove that as it comparable to Reddy, N. H., et al, finding that some but not all Acyclovir, Atenolol, and Ciprofloxacin Hydrochloride products met the biowaiver criteria [35]. Excipients and additives used in manufacturing tablets have great effects on their dissolution, therefore to achieve biowaiver according to regulatory rules, good manufacturing practice should be followed and careful selection of the excipients used is mandatory.…”
Section: Dissolution Studiesmentioning
confidence: 88%
“…Another study carried out in the United Arab Emirates in 2017 evaluated five multi-source products of amoxicillin/clavulanic acid tablets (875 mg/125 mg), finding that only three products were bioequivalent with the innovator based on dissolution profiles (i.e., releasing more than 85% of the amount declared in the first 15 minutes) (25). A study carried out in 2017 showed that of 10 multi-source products of ciprofloxacin (500 mg tablets; four from South Africa and six from India), only five (two from South Africa and three from India) were bioequivalent with the reference product because they met the bio-exemption criteria proposed by the WHO (26). Similar results were obtained by a study carried out in India in 2017, which evaluated dissolution and bioequivalence profiles in healthy volunteers, finding that a multi-source product of amoxicillin capsules (500 mg) was not bioequivalent with the reference product (27).…”
Section: Discussionmentioning
confidence: 99%
“…The FDA definition of high solubility is that the highest dose allowed for a single drug administration can be dissolved in 250 ml or less of an aqueous solution at 37℃ and pH1.0-7.5. The other regulatory bodies narrow the pH range to 1.2-6.8 or 1.0-6.8 [23]. In this study, we followed the classification from the World Health Organization.…”
Section: Different Bcs Classifications Have Been Developed By the Wormentioning
confidence: 99%